Pain Treatment in Thorax Malignities - Onal, Selami Ates (Bentham Science Publ, 2013)
Acute pain is a form of pain that starts suddenly. Chronic pain arises when pain continues after an acute disease or a reasonable recovery period. This period varies between 1 and 6 months. Visceral pain is an acute pain that develops depending on abnormal functioning or disorder of viscera or their membranes (parietal pleura, pericardia, peritonea). Lung cancer related pain depends on the location of the primary tumour, its regional invasion and metastatic spread. Pain may develop secondarily, depending on the peripheral growth of the primary tumour (spread to pleura or chest wall) or nerve invasion (pain which spreads to the arms or shoulders, known as Pancoast syndrome). While visceral pain is experienced slightly in the ipsilateral hemithorax independent of the regional spread, it may also cause non-specific chest pain symptoms. Pain may be located at the metastasis as with the bone metastases seen in one-third of patients and brain metastases, which progresses with headache and intracranial hypertension.
Keywords: Lung cancer; pain